Early Childhood Interventions Proven Results, Future Promise - Karoly, Lynn A. (RAND Corporation, 2005)
Considers the potential consequences of not investing additional resources in children's lives, the range of early intervention programs, the demonstrated benefits of interventions having high-quality evaluations, the features associated with successful programs, and the returns to society associated with investing early in the lives of disadvantaged children. The findings indicate the existence of a body of sound research that can guide resource allocation decisions.